Pengaruh Penerapan Model Pembelajaran Kepala Bernomor (Number Head Together) Terhadap Minat Dan Hasil Belajar Siswa Pada Sub Pokok Bahasan Fotosintesis Siswa Kelas VIII SMP Negeri 22 Surakarta Semester Genap Tahun Ajaran 2015/2016 - Setyaningrum, Afiah; , Dr. Sofyan Anif M.Si (2016)
This research conducted to know the influence of implementation number head together teaching model towards students' interests and learning result in sub topic photosynthesis students of SMP N 22 Surakarta grade VIII. The method used in this research is quasi-experiment, the sample taken by non-random technique sampling, Class VIII A as the experiment class and VIII B as controlled class. Techniques of collecting data used are interview, observation, documentation, survey and written test. The data is analyzed by precondition test technique and multivariate. The result of data analyzes shows the significance of learning interest is 0,000 and learning result 0,007 shows that its less than 0,05. It makes H0 rejected, means, there is an influence of teaching model. The average of students' interest and learning result in the experiment class NHT Model (the interest is 67,29 and learning result is 74,54) higher than the controlled class with the conventional learning (the interest is 59,23 and the learning result is 71,36). Based on this research, it can conclude that implementation of Cooperative Learning in Number Head Together type in sub topic photosynthesis gives an influence towards students' interest and learning result students of SMP N 22 Surakarta grade VIII.